Randomized Clinical Trial: Bone Bioactive Liquid Improves Implant Stability and Osseointegration - Ashraf Al Madhoun; Khaled Meshal; Neus Carrió; Eduard Ferrés-Amat; Elvira Ferrés-Amat; Miguel Barajas; Ana Leticia Jiménez-Escobar; Areej Said Al-Madhoun; Alaa Saber; Yazan Abou Alsamen; Carles Marti; Maher Atari (Journal of Functional Biomaterials)
Implant stability can be compromised by factors such as inadequate bone quality and infection, leading to potential implant failure. Ensuring implant stability and longevity is crucial for patient satisfaction and quality of life. In this multicenter, randomized, double-blind clinical trial, we assessed the impact of a bone bioactive liquid (BBL) on the Galaxy TS implant’s performance, stability, and osseointegration. We evaluated the impact stability, osseointegration, and pain levels using initial stability quotient (ISQ) measurements, CBCT scans, and pain assessment post-surgery. Surface analysis was performed using scanning electron microscopy (SEM) and atomic force microscopy (AFM). In vitro studies examined the BBL’s effects on dental pulp pluripotent stem cells’ (DPPSCs’) osteogenesis and inflammation modulation in human macrophages. All implants successfully osseointegrated, as demonstrated by the results of our clinical and histological studies. The BBL-treated implants showed significantly lower pain scores by day 7 (p < 0.00001) and improved stability by day 30 (ISQ > 62.00 ± 0.59, p < 8 × 10−7). By day 60, CBCT scans revealed an increased bone area ratio in BBL-treated implants. AFM images demonstrated the BBL’s softening and wettability effect on implant surfaces. Furthermore, the BBL promoted DPPSCs’ osteogenesis and modulated inflammatory markers in human primary macrophages. This study presents compelling clinical and biological evidence that BBL treatment improves Galaxy TS implant stability, reduces pain, and enhances bone formation, possibly through surface tension modulation and immunomodulatory effects. This advancement holds promise for enhancing patient outcomes and implant longevity.